Sketch : A Step-by-Step Guide for Absolute Beginners - Simmonds, Jackie (London Collins, 2001)
One in a series, this title should give even the most hesitant of beginners the enthusiasm and confidence to start sketching in a variety of media, including graphite pencil and charcoal, Conte and pastel pencils, watercolour soluble pencils and crayons, pen and ink markers and felt-tips.
Include Color Illustration
Keywords: Drawing--Technique